The role of Kisspeptin signaling in Oocyte maturation - Masumi, Saeed; Lee, Eun Bee; Dilower, Iman; Upadhyaya, Sameer; Chakravarthi, V. Praveen; Fields, Patrick E.; Rumi, M. A. Karim (Frontiers in Endocrinology, 2022)
Kisspeptins (KPs) are secreted by hypothalamic KP neurons and act on gonadotropin releasing hormone (GnRH) neurons. GnRH induces gonadotropins (GPNs), namely LH and FSH, from the anterior pituitary, which are essential for gonadal development, onset of puberty, and gonadal functions. KP-signaling represent a regulatory link between the gonadal steroid hormones and GPNs within the hypothalamic-pituitary-gonadal (HPG) axis. In clinical trials, KPs have been administered successfully to patients undergoing in vitro fertilization for increasing oocyte maturation. These neuropeptides regulate ovarian follicle development, steroidogenesis, and oocyte maturation through induction of hypothalamic GnRH and pituitary GPNs. However, KPs and KP receptors (KPRs) are also expressed in the ovaries. KPs are expressed predominantly in the granulosa cells (GCs) and the KPRs in the oocytes. Expression of KPs in the ovaries increases with the progression of estrous cycle and peaked with the preovulatory GPN surge. Moreover, intrafollicular levels of KPs rise with the advancement of follicle development and correlates with follicular estradiol concentration. These findings suggest that GC-derived KPs may act on the KPRs in oocytes during the preovulatory maturation. A recent study has demonstrated that the presence of KPR in murine oocytes is essential for proper development of ovarian follicles and maturation of oocytes. Selective loss of KPRs in oocytes leads to premature ovarian senescence. In addition to the intraovarian role of KP-signaling in oocyte maturation, a direct role of KPs have been identified during in vitro maturation of oocytes. KP-signaling in oocytes results in Ca2+ release and activates the MAP kinase ERK1/2. In vitro treatment of oocytes with KPs also upregulates mRNA levels of the factors that favors oocyte maturation. Understanding the direct in vivo or in vitro role of KP-signaling in oocyte maturation will help develop novel KP-based strategies to improve the assisted reproductive technologies.